Fisioterapia respiratória, capacidade de exercício e predição de mortalidade em pacientes com fibrose cística - Vendrusculo, Fernanda Maria (2018)
Introduction: Cystic fibrosis (CF) is a genetic, multisystemic disease characterized by progressive loss of lung function and airway obstruction. Thus, airflow limitation and dynamic hyperinflation may limit exercise capacity of these patients. In addition, exercise capacity has correlated with survival in children and adults with CF. Objective: To evaluate the effect of respiratory physiotherapy on exercise capacity and the role of maximal oxygen consumption as a predictor of mortality in CF patients. Methods: This thesis is divided into two articles. Article 1 was a prospective randomised, cross-over pilot study performed on children diagnosed with CF, aged >9 years and >128 cm tall. Two visits were performed with one month of interval, one with respiratory physiotherapy using positive expiratory pressure and autogenic drainage, before spirometry, plethysmography and the cardiopulmonary exercise test (CPET), and another without respiratory physiotherapy. The CPET was performed on a cycle ergometer using the Godfrey protocol. All tests followed international recommendations. Article 2 consisted of systematic review and meta-analysis, in which an online search was performed in PubMed, Embase, LILACS and SciELO databases. Were included cohort studies that assessed mortality rates after maximal oxygen uptake (VO2peak) measurements during CPET. The quality analysis of the selected articles was performed using the Newcastle-Ottawa scale. The main outcome evaluated was the mortality of CF patients. Whenever possible, and if appropriate, a random effect meta-analysis was performed. Results: Study 1 included 12 patients with CF with mean age of 12.83±1.85 years, body mass index in Z score was 0.08±0.82 and 75% of them presented at least one allele ΔF508. No significant differences were found in maximal oxygen consumption with respiratory physiotherapy. However, there was a significant decrease in minute ventilation (VE) and ventilatory equivalents for oxygen consumption (VEVO2) and for carbon dioxide production (VEVCO2) at lactate threshold when respiratory physiotherapy was performed prior to CPET. The mean VE (L.min-1) was 26.67± 5.49 vs 28.92±6.30 (p=0.05), VEVO2 (L.min-1) was 24.5±1.75 vs 26.05±2.50 (p=0.03) and VEVCO2 (L.min-1) was 26.58±2.41 vs 27.98±2.11 (p=0.03). In study 2, six cohort studies were included, totaling 551 participants. Five studies were classified with high methodological quality. Two different analyzes were carried out to evaluate the influence of VO2peak on mortality. The significant standardized total difference between the VO2peak averages in the survival or non-survival groups was -0.606 (95%CI= -0.993 – -0.219; p=0.002). In addition, patients with lower VO2peak were associated with a significantly higher mortality risk (RR: 4.896; 95%CI= 1.086 – 22.072; p=0.039). Conclusion: The results suggest that the performance of respiratory physiotherapy prior to exercise may lead to improved ventilatory dynamics during exercise in CF patients. In addition, the systematic review with meta-analysis has shown that low levels of maximal oxygen uptake are associated with an increase of 4.8 in the risk of mortality, indicating that VO2peak could also be an important follow-up variable.